INSTANTANEOUS POLARIZATION ATTRIBUTES BASED ON AN ADAPTIVE APPROXIMATE COVARIANCE METHOD - Diallo M.S.; Kulesh M.; Holschneider M.; Kurennaya K.; Scherbaum F. (My University, 2006)
We introduce a method for computing instantaneous-polarization attributes from multicomponent signals. This is an improvement on the standard covariance method (SCM) because it does not depend on the window size used to compute the standard covariance matrix. We overcome the window-size problem by deriving an approximate analytical formula for the cross-energy matrix in which we automatically and adaptively determine the time window. The proposed method uses polarization analysis as applied to multicomponent seismic by waveform separation and filtering. © 2006 Society of Exploration Geophysicists.
Keywords: GEOPHYSICAL SIGNAL PROCESSING; GEOPHYSICAL TECHNIQUES; SEISMIC WAVES; SEISMOLOGY